The increase of ecological safety in the Uranium production area of influence - V. I. Lyashenko (Известия высших учебных заведений: Геология и разведка, 2015)
The increase of ecological safety in the zone of Uranium production on the base of scientific justification, implementation and use of rehabilitation measurements for minimization of negative evidences on the environment and men’s health from the radiative factors. Radioecological research included: measurements of the power of exposure dose of γ-radiation with grid of 100x100 м и 20x10 м (walking γ-observation) on the 40 km2 square; analysis of the soils for the radioactive nuclides; water probe for the Radium and Uranium content assessment; definition of sum α- и β-activity of the soil; definition of the radon gas concentration in living rooms. The system of radiative monitoring of Uranium objects on the base of instruments and automatic systems of new generation.